Analisis Metode Altman Z-Score Dalam Memprediksi Kebangkrutan Perusahaan (Tahun 2016-2021) - Yuliyasari Br Ginting; Wardayani Wardayani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to detect the potential for bankruptcy early on at PT. Sumber Alfaria Trijaya Tbk. PT. Sumber Alfaria Trijaya Tbk is one of the leading retail companies in Indonesia, or commonly known as Alfamart, a trading company that sells units and retails related to household needs. This study uses the Altman Z-Score method. The Altman Z-score method is a tool used to predict the level of bankruptcy of a company by calculating the value of several ratios and then entering it into a discriminant equation. The results of this study were conducted in 2016-2021 where the Z-Score value was greater than 2.90, which means that the company is healthy or not bankrupt, so this can also prove that the Altman Z-score method is effectively used in assessing the level of bankruptcy in a company.